IEEE International Conference on Robotics and Automation, 2004. Proceedings. ICRA '04. 2004 2004
DOI: 10.1109/robot.2004.1307985
|View full text |Cite
|
Sign up to set email alerts
|

Image moments: generic descriptors for decoupled image-based visual servo

Abstract: To cite this version:O. Tahri, François Chaumette. Abstract-Moments are generic and (usually) intuitive descriptors that can be computed from several kinds of objects defined either from closed contours (continuous object) or a set of points (discrete object). In this paper, we propose to use moments to design a decoupled image-based visual servo. The analytical form of the interaction matrix related to the moments computed for a discrete object is derived, and we show that it is different of the form obtained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 7 publications
0
33
0
1
Order By: Relevance
“…Even if successful, all the required markers may not be visible in the field of view. Recent work, [21,22] has shown that image moments can be used as features for servoing, Avoiding the need for markers placed in the scene. We define the servoing task as bringing the root tip close to the center of the field of view.…”
Section: Image Processing For Visual Servoingmentioning
confidence: 99%
“…Even if successful, all the required markers may not be visible in the field of view. Recent work, [21,22] has shown that image moments can be used as features for servoing, Avoiding the need for markers placed in the scene. We define the servoing task as bringing the root tip close to the center of the field of view.…”
Section: Image Processing For Visual Servoingmentioning
confidence: 99%
“…In order to have a better and easier control over the robot trajectory, approximatively decoupled features are chosen as proposed in [3], [16]. Six visual features derived from the moments of the set of points have been chosen to control the six DOF of the robot.…”
Section: A Main Task Function Using Visual Servoingmentioning
confidence: 99%
“…The two first features are the position x g and y g of the center of gravity. Since the considered object is discrete, the third feature a is based on the centered moments of order 2 to control the range between the robot and the target, as proposed in [16]. The fourth feature α mainly rotates the camera around the optical axis.…”
Section: A Main Task Function Using Visual Servoingmentioning
confidence: 99%
“…Problems (18) and (17) have been solved through the function FMINSEARCH of MATLAB by evaluating α(C) andρ(C) as described in Section III-C. Problem (17) has been initialized with the solution of problem (18), and problem (18) has been initialized with C = 0 3×(δ−1) . Figure 1a shows the current and desired locations denoted by F and F * , and the observed features corresponding to the biggest white circles.…”
Section: Numerical Examplesmentioning
confidence: 99%
“…In partitioning methods, the degrees of freedom of the camera are grouped according to some criteria and differently controlled (see for example [9]- [11]). Other methods, such as visual servoing based on navigation functions [12], path-planning techniques [13]- [15], visual servoing invariant to the intrinsic parameters [16], visual servoing based on image moments [17] and methods based on the generation of circular-like trajectories [18], have been proposed in the literature.…”
Section: Introductionmentioning
confidence: 99%